Climate change: The necessary, the possible and the desirable Earth League climate statement on the implications for climate policy from the 5th IPCC Assessment. (17th December 2014) - Rockström, Johan; Brasseur, Guy; Hoskins, Brian; Lucht, Wolfgang; Schellnhuber, John; Kabat, Pavel; Nakicenovic, Nebojsa; Gong, Peng; Schlosser, Peter; Máñez Costa, Maria; Humble, April; Eyre, Nick; et al.
Abstract The development of human civilisations has occurred at a time of stable climate. This climate stability is now threatened by human activity. The rising global climate risk occurs at a decisive moment for world development. World nations are currently discussing a global development agenda consequent to the Millennium Development Goals (MDGs), which ends in 2015. It is increasingly possible to envisage a world where absolute poverty is largely eradicated within one generation and where ambitious goals on universal access and equal opportunities for dignified lives are adopted. These grand aspirations for a world population approaching or even exceeding nine billion in 2050 is threatened by substantial global environmental risks and by rising inequality. Research shows that development gains, in both rich and poor nations, can be undermined by social, economic and ecological problems caused by human‐induced global environmental change. Climate risks, and associated changes in marine and terrestrial ecosystems that regulate the resilience of the climate system, are at the forefront of these global risks. We, as citizens with a strong engagement in Earth system science and socio‐ecological dynamics, share the vision of a more equitable and prosperous future for the world, yet we also see threats to this future from shifts in climate and environmental processes. Without collaborative action now, our shared Earth system may not be able to sustainably support a large proportion of humanity in the decades ahead.